2018
DOI: 10.1089/cyber.2018.0435
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction: A Closer Look at Multidimensional Parenting Practices and Child Mental Health

Abstract: This study aimed to examine how both psychosocial variables (authoritative, authoritarian, and shaming, and parent-child relationships) and psychological symptoms were associated with Internet addiction, while controlling for the sociodemographic variable (child gender). A national proportionately stratified random sample of 6,233 fourth-grade primary school students in Taiwan participated in the study. Hierarchical regression models were performed to test the research hypotheses. The results show that psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…We found that adolescents’ ODD symptoms and Internet addiction were negatively associated with parental efficacy, whereas parental care was positively associated with parental self-efficacy in managing adolescent Internet use after accounting for several covariates. Our findings are consistent with transactional theory [ 4 ], which holds that children may play an active role in influencing parental behavior and self-efficacy, whereas parenting behaviors may also influence children’s externalizing behaviors and risks of Internet addiction [ 31 ]. Finally, the present study highlights the need for family-based interventions among adolescents with ADHD and the importance of recognizing signs and symptoms of Internet addiction, empowering and providing parents with parenting resources and tools, and improving parental self-efficacy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that adolescents’ ODD symptoms and Internet addiction were negatively associated with parental efficacy, whereas parental care was positively associated with parental self-efficacy in managing adolescent Internet use after accounting for several covariates. Our findings are consistent with transactional theory [ 4 ], which holds that children may play an active role in influencing parental behavior and self-efficacy, whereas parenting behaviors may also influence children’s externalizing behaviors and risks of Internet addiction [ 31 ]. Finally, the present study highlights the need for family-based interventions among adolescents with ADHD and the importance of recognizing signs and symptoms of Internet addiction, empowering and providing parents with parenting resources and tools, and improving parental self-efficacy.…”
Section: Discussionsupporting
confidence: 90%
“…According to transactional theory [ 48 ], a set of ongoing interactions between a child and parent results in the modification of each other’s behaviors. Although parenting behaviors influence children’s externalizing behaviors and risks of Internet addiction [ 31 , 49 ], children may also play an active role in influencing parental behaviors and self-efficacy. The results confirmed our hypothesis that the level of adolescent Internet addiction was negatively associated with parental self-efficacy in managing adolescent Internet use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This counterintuitive finding may actually reflect a reverse causality, i.e., parents simply engage in more restrictive behaviors after observing their children's addictive use of SNSs. Previous studies showed inconsistent findings where parental restrictive mediation was found to be positively ( 79 , 80 ), negatively ( 41 , 81 ), or insignificantly ( 82 ) related to their children's addictive use of Internet. Researchers have proposed that the association between parental mediation strategies and their children's behavior may be further moderated by other factors ( 37 , 82 84 ).…”
Section: Discussionmentioning
confidence: 88%
“…Formally speaking, internet addiction is the excessive use of time spent on internet activities that can cause a decrease in the psychological condition of individuals (both mental and emotional), behavioral disorders, and negative impacts on social interactions, work and daily life. Many children spend time with gadgets rather than socializing, making children in the current era prefer to use gadgets as their "playground" rather than playing outside with friends (Hsieh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%